An analysis on food consumption of households classified by income in rural China - Linhai MEI (Acta Agriculturae Slovenica, 2001)
In the paper analyzes influences on food consumption by households classified by income in rural China. The income-food consumption relationships (Engel functions) are estimated and income (demand) elasticities for food consumption are analyzed. The results display that income elasticity for grain has been very different among various income groups; for the most prosperous group, grain goods has become into abnormal goods, but for other groups grain goods are all normal goods. Decline of income elasticities meat by year imply stable meat consumption so that meat has become necessaries. Income elasticities for luxury foods both by year and by across section has been very higher, and their very higher R2 values mean the change in consumption of luxury foods depends strongly on income change. That is, Chinese rural households will continue to expend expenditure share in luxury foods as income increases.